The power of God against the guns of government religious upheaval in Mexico at the turn of the nineteenth century - Vanderwood, Paul J. (Stanford University Press, 1998)
"Writing in a narrative style reminiscent of Womack's Zapata and the Mexican Revolution, author explains a series of 1890s uprisings in Tom?ochic, in the border state of Chihuahua, against the Porfirians' determination to dictate who would control the land and the future. Pushed forward by the belief in folk saint Teresa Urrea, indigenous people and mestizos led by Cruz Ch?avez fought government troops to preserve their way of life. Surprisingly, author makes no mention of another such movement in Brazil occurring at the same time, which was immortalized first by Da Cunha and then by Vargas Llosa"--Handbook of Latin American Studies, v. 58.